2000
DOI: 10.1038/35016083
|View full text |Cite
|
Sign up to set email alerts
|

Induction of neurogenesis in the neocortex of adult mice

Abstract: Neurogenesis normally only occurs in limited areas of the adult mammalian brain--the hippocampus, olfactory bulb and epithelium, and at low levels in some regions of macaque cortex. Here we show that endogenous neural precursors can be induced in situ to differentiate into mature neurons, in regions of adult mammalian neocortex that do not normally undergo any neurogenesis. This differentiation occurs in a layer- and region-specific manner, and the neurons can re-form appropriate corticothalamic connections. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
804
3
18

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,117 publications
(861 citation statements)
references
References 31 publications
36
804
3
18
Order By: Relevance
“…The two primary zones of adult proliferation are the subgranular layer of the hippocampal dentate gyrus and the SVZ of the forebrain, although other zones are also thought to exist 51,52 . DCX has become a widely used marker for newly generated neuroblasts in proliferative zones in adult 14,31,53,54 .…”
Section: Role Of DCX In the Rmsmentioning
confidence: 99%
“…The two primary zones of adult proliferation are the subgranular layer of the hippocampal dentate gyrus and the SVZ of the forebrain, although other zones are also thought to exist 51,52 . DCX has become a widely used marker for newly generated neuroblasts in proliferative zones in adult 14,31,53,54 .…”
Section: Role Of DCX In the Rmsmentioning
confidence: 99%
“…Our own results demonstrate a complete absence of constitutively occurring neurogenesis in murine neocortex (Magavi et al 2000). However, two studies reported low level, constitutively-occurring neurogenesis in specific regions of the neocortex of adult primates (Gould et al 1999c) and in the visual cortex of adult rat (Kaplan 1981).…”
Section: Cortical Neurogenesismentioning
confidence: 47%
“…Many adult precursors are capable of migrating long distances, using both tangential and radial forms of migration (Lois and Alvarez-Buylla 1994;Doetsch and Alvarez-Buylla 1996;Luskin and Boone 1994). Endogenous adult neural precursors are also capable of extending axons significant distances through the adult brain (Magavi et al 2000;Barber 1982;Crews and Hunter 1994). In addition, in vitro and in vivo experiments have begun to elucidate the responses of endogenous precursors to both growth factors and behavioral manipulations, and are beginning to provide key information toward manipulation of their proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations